The Influence Of Learning Motivation And Teaching Presence On Academic Performance: A Study On Students Of Ciputra Makassar University - Budiman, Maydelaine Gabrielle; Fania Yuniar Laude; Samuel Elmer Limputra; Carolina Novi Mustikarini (Accounting Profession Journal (APAJI), 2025)
This study was conducted on students of Ciputra University Makassar to explore the influence of learning motivation and teaching presence on academic performance. The primary objective of this research is to analyse how students' motivation to learn affects their engagement with instructors and how the presence of instructors further influences their overall performance. Additionally, the study examines whether learning motivation has a direct impact on student performance. A total of 70 students participated in this study, providing valuable data for analysis. During the research period, all students were engaged in face-to-face learning, which allowed for direct observation of interactions between students and instructors. The study utilized the Partial Least Squares (PLS) method for data analysis, a statistical approach commonly used to measure complex relationships between multiple variables. The findings of this research indicate that learning motivation significantly influences teaching presence, suggesting that highly motivated students are more engaged with their instructors. Furthermore, teaching presence has a significant positive impact on academic performance, highlighting the crucial role of instructors in facilitating student success. Lastly, the results reveal that learning motivation also has a direct and significant effect on performance, emphasizing the importance of fostering a strong motivation to learn among students. These results provide valuable insights for educators and institutions, suggesting that enhancing both student motivation and instructor presence can lead to improved learning outcomes. Future research could explore additional factors that may contribute to student performance, such as learning environment, peer interaction, and teaching strategies.